Lignocellulosic biomass: insights into enzymatic hydrolysis, influential factors, and economic viability - Priyanka Basera; Shuchishloka Chakraborty; Neha Sharma (Discover Sustainability)
Abstract Lignocellulosic biomass (LB) represents a sustainable and abundant feedstock with diverse applications, particularly in microbial fermentation processes for the production of biofuels and biochemical. This biomass serves as a promising alternative to conventional fossil fuels. Extensive research on the decomposition of wood has elucidated various microbial enzymatic and non-enzymatic mechanisms that facilitate the utilization of this resource. This review systematically examines the chemical and structural factors contributing to biomass recalcitrance, emphasizing recent advancements in analytical tools for their assessment. Furthermore, we explore innovative predictive models for hydrolysis, which are crucial for optimizing the conversion of LB into biofuels and bio-based chemicals. A comprehensive cost analysis of hydrolysis processes is also presented, offering insights into the economic feasibility of these conversion methods. The findings underscore the potential of lignocellulosic biomass as a key player in sustainable energy and material production.